In-situ measurement of surface relief induced by Widmanstätten and bainitic ferrites in low carbon steel by digital holographic microscopy. (15th March 2019) - Komine, Shuhei; Sekido, Kenji; Inoue, Junya
Abstract: In-situ measurement by digital holographic microscopy (DHM) was employed to clarify the difference between the surface relief effects of Widmanstätten ferrite (WF) and bainitic ferrite (BF) associated with their transformations from austenite in a low-carbon steel. It was clarified that the evolution of the surface relief is totally different between WF and BF. Only in BF, the observed ratio of the relief height to the plate width converged instantly to the value predicted by the phenomenological theory of martensite crystallography (PTMC). The ratio gradually increased with increasing plate thickness and never reached the value predicted by PTMC in WF. Graphical abstract: Unlabelled Image